El Marqués de Salamanca y la amortización - Sánchez García, Raquel (Cuadernos de Historia Contemporánea, 2003)
The rail companies were deeply affected by the economic crisis of 1866. The businessmen and the investors, pressed by their losses, asked the government about a way to face the problem. One of them, José de Salamanca, wrote a letter to the president Ramón Narváez suggesting him a project whereby the government took charge of the railways. This article analyses Salamanca’s project in the context of the aforemetioned crisis.